Molecular characteristics and potential therapeutic targets in Merkel cell carcinoma. Issue 5 (27th January 2016) - Mauzo, Shakuntala H; Ferrarotto, Renata; Bell, Diana; Torres-Cabala, Carlos A; Tetzlaff, Michael T; Prieto, Victor G; Aung, Phyu P
Abstract : Merkel cell carcinoma (MCC) is an aggressive neuroendocrine skin tumour occurring preferentially in elderly and immunosuppressed individuals. Multiple studies have provided insight into the molecular alterations of MCC, leading to the design of several ongoing clinical trials testing chemotherapy, targeted therapy and immunotherapy in patients with recurrent or metastatic disease. The results of some of these studies are available, whereas others are eagerly awaited and will likely shed light on the understanding of MCC biology and potentially improve the clinical outcomes of patients with this rare disease.